Colostrum avoidance and associated factors among mothers of less than 6-month-old children in Dilla town, Southern Ethiopia - Gashaw, Anteneh; Kebede, Daniel; Regasa, Teferi; Bekele, Hermela (Frontiers in Pediatrics, 2024)
Background: Colostrum, often referred to as "golden milk," is the initial milk produced after birth, crucial for preventing childhood malnutrition and boosting natural immunity. Neglecting colostrum intake heightens the vulnerability to infections and mortality, particularly in developing regions. Colostrum avoidance is prevalent in Ethiopia. This research aimed to investigate the frequency and factors contributing to colostrum avoidance in Dilla town, southern Ethiopia.M ethod: A community-based cross-sectional study was carried out in late 2023. Data were gathered from 350 participants, selected through multistage sampling, using structured questionnaires and face-to-face interviews. Data entry was conducted using Epi Data version 4.2.0 and transferred to Stata version 18 for analysis. Bivariate and multivariable logistic regression analyses were employed to identify factors associated with colostrum avoidance, with a significance level of p < 0.05.Result: The prevalence of the colostrum avoidance was 28.3% (95% CI: 18.4%-38.2%). Late initiation of breastfeeding (AOR 4.15 95% CI 2.51-6.84), pre-lacteal feeding, non-use of postnatal care (PNC) (AOR 1.79 95% CI 1.05-3.04), and lack of information about colostrum (AOR 1.88 95% CI 1.14-3.08) were factors significantly associated with the colostrum avoidance.Conclusions and recommendations: A high prevalence of colostrum avoidance was observed, with pre-lacteal feeding, delayed initiation of breastfeeding, lack of PNC, and inadequate maternal knowledge about colostrum identified as contributing factors. Consequently, interventions aimed at reducing colostrum avoidance should prioritize improving access to and promotion of PNC, promoting timely initiation of breastfeeding, and intensifying awareness campaigns highlighting the advantages of colostrum while emphasizing the risks associated with pre-lacteal feeding.Background: Colostrum, often referred to as "golden milk," is the initial milk produced after birth, crucial for preventing childhood malnutrition and boosting natural immunity. Neglecting colostrum intake heightens the vulnerability to infections and mortality, particularly in developing regions. The objective of this research is to investigate the frequency and contributing factors of avoiding colostrum consumption in Dilla town, located in the Gedeo zone, southern Ethiopia.